QUANTIFICATION OF RESIDUAL CLOVE OIL, BENZOCAINE AND TRICAINE IN FISH FILLETS USING SPE AND UPLC-DAD - Pereira, Robson A.; Saczk, Adelir A.; Okamura, Daniel; Cardoso, Maria das Graças; Costa, Leandro S.; Santiago, Wilder D.; Souza, Thallis M.; Lima, Rafael M. Felix De; Rosa, Priscila V. E (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
Residual quantification of the anesthetics clove oil (CO) – isoeugenol (ISO), eugenol (EUG) and methyleugenol (MET) –, benzocaine (BZN) and tricaine (MS-222) was made in fillets of two fish species: Nile tilapia (Oreochromis niloticus) and a catfish hybrid, cachadia (Pseudoplatystoma reticulatum x Leiarius marmoratus). Samples (n=4) of each fish were evaluated after submitted to anesthesia in five dosages defined based on the induction time of each species after depuration times (0h, 12h, 24h and 48h). Different methodologies of sample preparation were tested and selected according to the better recovery. The quantification of anesthetics was performed by UPLC-DAD. The variance of residual means among anesthetics, dosages and fish species was compared. After anesthesia (0h) both species, tilapia and cachadia, presented residual anesthetics. Fishes depurated during 12h, 24h and 48h did not present detectable values, it means, values were below the limits of detection. BZN presented the highest mean residual concentration for tilapia and cachadia (p=0.01), while MS-222 presented the lowest residual amounts in tilapias and EUG in cachadias, what may be related to the metabolism and carcass composition of each fish species. There were no significant differences among the five dosages, except the lowest MS-222 concentration in tilapias that resulted in higher residual concentrations because low dosages increase the induction time and consequently the permanence of the fish in anesthesia. Ultimately, mean values of residues in cachadia were higher than in tilapia, and MS-222 and EUG presented the lowest residual values for tilapia and cachadia, respectively.